Language and nutritional education. Results of a population survey - Tejedor Martín, Francisco Javier; Pérez Llano, Begoña; Mijancos Gurruchaga, María Teresa; Gonxález Panero, Pilar (Revista Española de Comunicación en Salud, 2019)
It is intended to assess the use and meaning of food-related expressions in Spanish language such as «comida basura» (junk food), «guarrerías» or «snacking». Methodology: A questionnaire has been developed and answered by residents in Spain. Results: An identification has been observed between the expressions «junk food» and «fast food», and a high agreement between «junk food» and «unhealthy food». The main foods included in this term are «refreshing drinks», followed by «hot dogs», «hamburger», «chips» and «pizza». There is broad agreement that the reason «food» is called «junk» is because it «promotes obesity», and because «it can cause cardiocirculatory problems». The term «guarrerías» related to food is known by 96.3% of surveyed, is related to foods such as «candies», «goodies», «buns», «chips», «salty snacks» or «popcorn». The consumption of «guarrerías» is associated with «unhealthy food». «Snacking» is only known by 52.87% of participants, is related to «eat between meals» and «habitual consumption of snacks». Conclusion: The use of expressions such as «junk food» (comida basura) or «guarrerías» can be useful in nutritional and health education.